Willingness to pay for cancer genetic testing in a tertiary healthcare centre - Azimatun Noor Aizuddin; Syed Rusli SAS; Abdul Rahman Ramdzan; Sharifah Azween Syed Omar; Zuria Mahmud; Zarina Abdul Latiff; Shamsul Azhar Shah; Salleh Amat; Fuad Ismail; Keng, Wee Teik; Ch Ng, Gaik Siew; Haniza Rais; et al. (International Islamic University Malaysia, 2021)
Increasing use of predictive genetic testing to address hereditary cancer risk has been commonly assessed by cost sharing practices. Little is known about how demographics, knowledge, attitude and practices may influence these individuals’ willingness to pay for cancer genetic testing. The objective of this research was to determine factors associated with willingness to pay for cancer genetic testing. A self-administered questionnaire was distributed to 175 respondents in the oncology and day care unit in one of tertiary healthcare centre. The respondents comprised cancer patients, their family members and the community. A total of 117 (66.9%) participants were willing to pay for cancer genetic testing. Ninety three (79.5%) of respondents were willing to pay from their own pocket with a mean of MYR1201.77 (SD976.72) and 95 (54.3%) respondents were willing to pay, shared with insurance. There were significant associations between willingness to pay with status of respondent as patients or family members or community, gender, race, educational level, income, knowledge and attitude. This is the first study to evaluate factors associated with willingness to pay not only among cancer patients but also their family members and the community. These findings reveal that majority of respondents believe there is valuable personal benefit based on genetic risk information and they are willing to pay for it.